1991
DOI: 10.2190/pwdp-45l8-lhl5-2vx7
|View full text |Cite
|
Sign up to set email alerts
|

Which Comes First the Simulation or the Lecture?

Abstract: Research into the instructional effectiveness of computer-based simulations has yielded inconsistent results. Part of this inconsistency can be attributed to the inappropriate instructional roles for which simulations are used. Two of the most promising roles of simulations in instruction are to: 1) establish a cognitive framework or structure to accommodate further learning in a related subject area, and 2) provide an opportunity for reinforcing, integrating and extending previously learned material. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…The third point of interest is that the place of simulations in the curriculum should be investigated. Lavoie and Good (1988) suggest that a "Piagetian" approach should be used, which implies that simulations are introduced in a first phase of learning where exploration is allowed, that concepts are formally introduced later, finally followed by concept application (see also Brant et al, 1991;White, 1993). This suggests a potential use of computer simulation that differs from the classical hypothesis driven approach.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third point of interest is that the place of simulations in the curriculum should be investigated. Lavoie and Good (1988) suggest that a "Piagetian" approach should be used, which implies that simulations are introduced in a first phase of learning where exploration is allowed, that concepts are formally introduced later, finally followed by concept application (see also Brant et al, 1991;White, 1993). This suggests a potential use of computer simulation that differs from the classical hypothesis driven approach.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Conceptual models still cover a wide range of model types such as qualitative vs. quantitative models, continuous vs. discrete, and static vs. dynamic models (see Van Joolingen & De Jong, 1991a). Models may also differ considerably in complexity, and range from very simple straightforward models, e.g., simple Mendelian genetics (Brant, Hooper, & Sugrue, 1991) to very complex models, e.g., the medical simulation HUMAN (Coleman & Randall, 1986) in which 200 variables and parameters can be changed. Also, specific characteristics like the place of variables in the model, or the distance between theoretical and operational variables characterize the conceptual model (Glaser, Schauble, Raghavan, & Zeitz, 1992).…”
Section: Simulations Of Conceptual Domainsmentioning
confidence: 99%
“…Whiteside (1985/86) has claimed that " ... many games and simulations can be used to foster in individuals some process related skills such as decision making" (p.116). Brant, Hooper and Sugrue (1991), in a review of educational simulations, concluded "Research conducted over the past two decades on the effectiveness of instructional simulations has yielded less than encouraging results" (p.469). Little research to date however, appears to focus on the use of simulations to develop generalised decision-making skills, that is, to produce better decision makers.…”
mentioning
confidence: 99%
“…In order to set the cognitive stage for students' future learning, simulations can be used effectively for the introduction of challenging or unfamiliar concepts (Brant, Hooper, & Sugrue, 1991;Windschitl, 1998). Simulation use as a preparatory activity can function as a conceptual model that helps students to better understand and encode information.…”
Section: Computer Simulations and Laboratory Activitiesmentioning
confidence: 99%
“…Students who are confronted with such a model during a preparatory activity are eventually more likely to remember the information and to reason with the principles learned in transfer situations (Akpan, 2001). When using simulations as an activity after laboratory experiments or instruction, simulations can support integration of acquired basic conceptual understanding into meaningful associations (Brant et al, 1991;Windschitl, 1998). However, confronting students with a simulation afterward can cause the students to have difficulty in assimilating the information based on the simulated model.…”
Section: Computer Simulations and Laboratory Activitiesmentioning
confidence: 99%